2005
DOI: 10.1080/08880010590964291
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Megadose Methylprednisolone Therapy on the Immune System in Childhood Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is a frequently encountered disease in childhood. Recent reports pointed to the benefit of high-dose steroid in ITP treatment since it resulted in a better outcome in a shorter time than IV immunoglobulin therapy. In the authors' clinic, mainly after 1984, megadose methyl prednisolone (MDMP) has been used for ITP treatment. There is no report that includes an extensive immune system examination of megadose steroid effect in childhood ITP. The purpose of this study is to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…After 1 week of MDMP therapy, the absolute lymphocyte count, lymphocyte subtype absolute numbers, and immunoglobulin A/G/M titers were found increased. 51 Our results were supported by Wilckens and De Rijk 17 who reported that GCs not only suppress but also enhance immune function.…”
Section: Effect Of Mdmp In Idiopathic Thrombocytopenic Purpurasupporting
confidence: 92%
See 1 more Smart Citation
“…After 1 week of MDMP therapy, the absolute lymphocyte count, lymphocyte subtype absolute numbers, and immunoglobulin A/G/M titers were found increased. 51 Our results were supported by Wilckens and De Rijk 17 who reported that GCs not only suppress but also enhance immune function.…”
Section: Effect Of Mdmp In Idiopathic Thrombocytopenic Purpurasupporting
confidence: 92%
“…[47][48][49] Our study of the effect of MDMP treatment on the immune system responses of patients with ITP revealed that MDMP led to improvement, whereas conventional dose prednisolone was inhibitory. 50,51 Twenty-nine patients (18 acute, 11 chronic ITP) were the subject of the study. After 1 week of MDMP therapy, the absolute lymphocyte count, lymphocyte subtype absolute numbers, and immunoglobulin A/G/M titers were found increased.…”
Section: Effect Of Mdmp In Idiopathic Thrombocytopenic Purpuramentioning
confidence: 99%